IMPLEMENTATION OF TYPES AND MODELS OF EDUCATIONAL SUPERVISION AT SMPN 3 CISARUA, WEST BANDUNG REGENCY - Kartini Nurhidayah; Diding Nurdin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
The implementation of academic supervision based on coaching has become an essential strategy to enhance the quality of education by improving teachers' professionalism and instructional practices. This study was conducted to explore the types and models of coaching-based academic supervision implemented at SMPN 3 Cisarua, as well as its impact on teacher performance. The urgency of this research lies in the need for transformative supervisory practices that promote teacher growth through reflective and collaborative approaches. Using a qualitative case study method, data were collected through in-depth interviews with the principal and teacher leaders and analyzed using thematic coding with the ATLAS.ti application. The results revealed ten thematic categories reflecting coaching-based supervision practices, including goal setting, active listening, empowering dialogue, feedback, reflection, and follow-up support. The coaching supervision model applied by the principal and teacher leaders showed a positive influence on pedagogical improvement, motivation, and the development of a professional learning culture. It also shifted the supervisory relationship from hierarchical to collegial. In conclusion, coaching-based academic supervision at SMPN 3 Cisarua proved effective in fostering teacher competence and collaboration. Therefore, its broader implementation is recommended in other schools to promote sustainable educational improvement.